Experimental Investigation of Influence of Acoustic Wave on Vapour Precipitation Process - Vekteris, V.; Tetsman, I.; Moksin, V. (Engineering, Technology & Applied Science Research, 2013)
The measurement results of acoustic field parameters above electroplating bath, in presence of water vapour, are analyzed in this work. Suction was created by means of side exhausters. It is obtained that the sound field generator generated a sound level of 130–140 dB at frequency interval between 1 and 10 kHz. It is shown that aerosol coagulation and precipitation processes are intensified under the mentioned conditions. The concentration of vapour and other aerosols in removal air decreases as a result, therefore air cleaning equipment costs can be reduced and cleaning efficiency increased.